Genetic linkage of autosomal recessive canine narcolepsy with a mu immunoglobulin heavy-chain switch-like segment. - Mignot, E (1991)
Identification of genes determining narcolepsy susceptibility is important not only for understanding that disorder but also for possible clues to general sleep-control mechanisms. Studies in humans reveal at least one such gene related to the major histocompatibility complex and in dog an as-yet-unmapped single, autosomal recessive gene canarc-1. Gene markers for canarc-1 were therefore sought by DNA restriction fragment length polymorphisms in our colony of narcoleptic dogs. A human mu-switch immunoglobulin probe and the enzyme Hae III identified a gene cosegregating with canarc-1 in backcrossed animals (logarithm of odds scores: m = 24, Z max = 7.2 at theta = 0%). canarc-1 was also shown not to be tightly linked with the dog major histocompatibility complex (m = 40, Z less than -2 at theta less than 4.8%). These results represent the mapping of a non-major histocompatibility complex narcolepsy gene and strongly suggest involvement of the immune system in the pathophysiology of that disease.